Thermoelectric Properties of Solution-Processed n-Doped Ladder-Type Conducting Polymers - Wang, Suhao (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.